Palliative care in elderly people: a literature review (Research, Society and Development, 2020)
This study aims to analyze the peculiarities of palliative care in the elderly and the challenges faced by the nursing professional. A non-systematic literature review was carried out, with a qualitative approach. At the end of the study, it can be seen that palliative care is on the rise in the country, increasingly reaffirming the importance of a multidisciplinary team in this care, with the need for health and social support actions, in addition to the implementation of public policies directed at these individuals, with a view to promoting health and preventing diseases, as well as the possibility of minimizing overload and enhancing the quality of life of these individuals. It is also noteworthy that the elderly need active observation for the vulnerabilities brought about by advancing age, as well as cultural and social issues that must be considered for decision making in relation to palliative care.